A systematic literature review concerning the different interpretations of the role of sustainability in project management - Kevin Friedrich (Management Review Quarterly, 2021)
The concept of sustainable development is widely accepted as one of the most important topics of our time. Although significant research has already been conducted within the field of integrating sustainability into project management, different interpretations of the role of sustainability appear. This is a major issue for the scientific community, as due to these varying interpretations it is difficult to put publications into context; accordingly, it might lead to communication issues within the community. With this research study we want to help solve this issue. We conduct a systematic literature review and identify 293 relevant publications. Using a synthesis approach based on grounded theory, we define three different categories of interpretations of the role of sustainability in the current state of research. The literature is then assigned back to these interpretations. Following this approach we are not only able to review the development of each interpretation over time, but also to identify that many publications contain multiple interpretations. Based on our findings, we give recommendations for the reflection of the existing literature, the writing of new publications and communication in the research field. We also redefine the concept of 'sustainable project management' based on a major theoretical characteristic we synthesise during our grounded theory approach to give guidance to future researchers.
Keywords: M10; M14; O22; Q01; Q56; 650; Sustainable project management; Systematic literature review; Sustainability; Project management